Początki życia ludzkiego w komentarzach patrystycznych - Roman Sala (Polonia Sacra)
The article “The Origins of the Human Life in Patristic Comments” tries to show the richness of thoughts and ideas presented by various writers in the early times of Christianity. Their views dealt with the prenatal stadium of a human being. Among main matters concerning the beginning of the human life analyzed by first Christian writers were: time of animation (the moment of union of the body and soul), abortion, the status of the human embryo, pre-existence of the soul referring to the belief that each individual human soul exists before conception, the origin of the soul. Among these issues, very present and lively discussed in the communities of early Christians, we can also find the reflection concerning the embryonic stages of Christ’s life.